A Security Paradigm for IoT - Anurag Urla, Priyanka; N Pai, Smitha; Mohan, Girish (International Journal of Engineering and Technology, 2018)
Current technology is offering lot of services at the finger tips. IoT is becoming a part of daily life without us being actually aware of the vulnerability to attacks. In this paper issues with choice of security algorithm is discussed. A secure computational approach is designed to overcome the issues with security.Â Â